Midterm Fate of the Contralateral Foot in Charcot Arthropathy. (October 2020) - Waibel, Felix W. A.; Berli, Martin C.; Gratwohl, Viviane; Sairanen, Kati; Kaiser, Dominik; Shin, Laura; Armstrong, David G.; Schöni, Madlaina
Background: The contralateral foot in Charcot arthropathy or neuroarthropathy (CN) is subject to increased plantar pressure. To date, the clinical consequences of this pressure elevation are yet to be determined. The aim of this study was to evaluate ulcer and amputation rates of the contralateral foot in CN. Methods: We abstracted the medical records of 130 consecutive subjects with unilateral CN. Rates of contralateral CN development and recurrence, contralateral ulcer development, and contralateral amputations were recorded. Statistical analysis was performed to identify possible risk factors for contralateral CN and ulcer development, and contralateral amputation. Mean follow-up was 6.2 (SD 4) years. Results: After a mean of 2.5 years, 19.2% patients developed contralateral CN. Female gender was associated with contralateral CN development (odds ratio 3.13, 95% confidence interval 1.27, 7.7). Overall, 46.2% patients developed a contralateral ulcer. Among the patients who developed contralateral CN, 60% developed an ulcer. Sanders type 2 at the index foot (midfoot CN) was significantly associated with contralateral ulcer development. Ulcer-free survival (UFS) differed significantly between patients with diabetes type 1 (median UFS 5131 days) and patients with diabetes type 2 (median UFS 2158 days). A total of 25 amputations had to be performed in 22 (16.9%) patients. Three of those 22 patients (2.3%) needed major amputation. Conclusion: Almost 20% of patients developed contralateral CN. Nearly half of people with CN developed a contralateral foot ulceration. Patients with type 2 diabetes had significantly shorter UFS than patients with diabetes type 1. Every sixth patient needed an amputation, with the majority being minor amputations. The contralateral foot should be monitored closely and included in the treatment in patients with CN. Level of Evidence: Level IV, retrospective study.